RELATIONSHIP OF NUTRITION FULFILLMENT AND ANXIETY LEVEL WITH BREAST MILK EXPENDITURE IN POST PARTUM MOTHERS AT PMB NELLY MARIANA HARAHAP PADANGSIDIMPUAN - Harahap, Dewani; Pebrianthy, Lola; Dewi, Sri Sartika Sari (JURNAL IBU DAN ANAK, 2021)
Breastfeeding mothers need adequate nutrition for the health of their bodies and babies. Psychological disorders in the mother cause reduced breastfeeding. This study aims to determine the relationship between nutritional fulfillment and anxiety levels with breastfeeding in post-partum mothers at PMB Nelly Marlina Harahap, Panyanggar Village, Padangsidimpuan Utara District in 2021. This type of research uses a cross-optional design study. The population in this study were 30 post partum mothers who gave ASI to their babies. Nelly Marlina Harahap with a sample size of 30 people. The sampling technique is total sampling. The results showed that there was a relationship between nutritional fulfillment (p value = 0.025) and anxiety level (p value = 0.001) with breastfeeding for post partum mothers at PMB Nelly Padangsidimpuan City in 2021. The conclusion was that there was a relationship between nutritional fulfillment and anxiety levels with expressing breastmilk in post partum mothers. It is hoped that mothers increase their knowledge about the fulfillment of nutrition in post partum mothers so that mothers can produce lots of breast milk and maintain a good psychological condition so that excessive stress does not occur.